My girl, old girl: Keywords, Collocations and Gender in British Children’s Fiction - Poynter, Elizabeth (Universitas Sanata Dharma, 2024)
The importance of children’s literature in the development of gender roles and gender identity is widely acknowledged. In the mid twentieth century books were the primary medium for most children, and the popular British fiction of the period is often considered to present strong gender stereotypes, despite the enormous social changes taking place (World War II, the Women's Movement). This study builds on previous content analysis and small-scale linguistic analysis to explore the extent of such stereotyping. It uses two digitised corpora, one of adventure books aimed at girls and boys, and the other of books for girls, from the period 1930-1970. With the corpus linguistics software LancsBox it examines keywords of each corpus against the other, and further against a contemporary (1961) corpus of general English prose. It then looks at collocations of GIRL, BOY, WOMAN, MAN. While there are some distinctions between the two genres, there are also considerable similarities. Some gender stereotyping occurs in use of reporting verbs and physical description, but there is no clear polarisation of gender roles in the collocations, and females are referenced more frequently in the adventure texts than in general prose of the same period. This tends to support previous findings, that the popular children's literature of this period is more nuanced than is often assumed.